A Mixed-Methods Needs Analysis for Interactive Multimedia-based Arabic Teaching Materials for Grade 8 at State Islamic Junior High School (MTsN) 17 Tanah Datar - Al Husna, Lathifah; Ulum, Mohammad Samsul; Rosyidi, Abdul Wahab; Hilmi, Mustafiqul (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aims to analyze students' needs for interactive multimedia-based Arabic teaching materials in grade 8 State Islamic Junior High School (MTsN) 17 Tanah Datar, West Sumatra. Arabic language learning uses textbooks that are still textual and monotonous without any accompanying teaching materials that are interesting and interactive. The approach used was a mixed method, data was collected from 36 students and teachers through interviews, classroom observations, and needs analysis questionnaires. The results of the interviews show that learning Arabic still faces obstacles in the form of conventional and less interesting teaching materials, exercises that have not touched listening and speaking skills, and limited access because it is only available in print form without the support of interactive technology. Observation data shows that Arabic learning is still dominated by teachers with lecture methods, students tend to be passive, interaction and language skills practice are minimal, and only rely on textbooks without media or supporting teaching materials. The results of the questionnaire showed that the majority of respondents (84.65%) strongly supported the development of Arabic teaching materials based on interactive multimedia. This study recommends developing interactive multimedia-based Arabic teaching materials that combine text, audio, video, animation, and self-directed exercises, specifically designed based on students’ real needs to support more engaging and interactive learning. As a practical implication, a prototype or unit template is proposed that integrates short texts, audio narration, micro-videos, and self-checking quizzes for the next stage of development.